Ընդդիմադիր կուսակցությունների ձևավորման գործընթացը և երկբևեռ քաղաքական համակարգի դրսևորումները Հայաստանում - Սարգսյան Ալեքսանդր (YSU Journal of International Affairs, 2015)
The subjects of the article are the problem of the formation of oppositional political parties in Armenia andthe features of bipolar political systems. The situation in the final period of the USSR’s history is presented during which anti-Soviet political groups leaded by Karabakh committee struggled against Communist party and Soviet Regime. The concept of constitutional reforms adopted by the Specialized Commission for Constitutional Amendments adjunct to the RA President is also analyzed in the article. Particularly the attention is focused on the issues of the principle of separation of power, checks, and balances, electoral systems as well as the role of political opposition.